Mental Resilience of Polish Adolescents During the COVID-19 Pandemic in 2021 - Oszwa, Urszula (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
Introduction. As reported in the literature, the severity of anxiety and depression symptoms in students due to social isolation during the COVID-19 pandemic prompted research on the psychosocial resources of adolescents, which was revealed in the form of resilience. Research Aim. Answers were sought to three research questions concerning: a) the resilience of Polish adolescents during the pandemic in 2021, b) the differentiation within the measured components of resilience, and c) the comparison of resilience between female and male students. Method. The electronic version of the Polish Mental Resilience Scale (SPP-18), standardised in the group of Polish adolescents and teenagers aged 12–18, was used for the online assessment of n = 263 students (F = 137; M = 126) aged 12–16. Results. The analysis of the students’ responses indicates the raised level of their resilience in the pandemic (7/10 in standard ten), differentiation within the components with the highest score for the sense of humour and the lowest for negative affect tolerance. Differences in the level of resilience due to gender were statistically insignificant, although the results of girls were slightly higher in all dimensions compared to those of boys. Conclusion. The raised level of resilience in the assessed sample seems optimistic, especially with respect to the majority of the students (about 70%). However, about 10% of the students in each of the 18 items declared low personal resilience competencies. Such groups of adolescents should be looked after, and if possible, periodically re-assessed to observe the changes in their level of resilience over time.